Prospective multicentre randomised trial comparing the efficacy and safety of single-anastomosis duodeno–ileal bypass with sleeve gastrectomy (SADI-S) versus Roux-en-Y gastric bypass (RYGB): SADISLEEVE study protocol - Delphine Maucort-Boulch; Maud Robert; Tigran Poghosyan; Dominique Delaunay; Elise Pelascini; Sylvain Iceta; Adrien Sterkers; Charles Barsamian; Litavan Khamphommala; Sylvie Bin Dorel; Sebastien Czernichow; Emmanuel Disse (BMJ Open)
Introduction Despite the non-negligible weight loss failure rate at midterm, Roux-en-Y gastric bypass (RYGB) remains the reference procedure in the treatment of morbid obesity with metabolic comorbidities. A recently emerged procedure, the single anastomosis duodeno–ileal bypass with sleeve gastrectomy (SADI-S), could be more effective on weight loss with similar morbidity and lower weight loss failure rate than RYGB. We propose the first randomised, open, multicentre superiority trial comparing the SADI-S to RYGB (SADISLEEVE).Methods and analysis The main objective is to demonstrate the superiority at 2 years after surgery of the SADI-S compared with RYGB in term of excess weight loss percentage. The secondary objectives are the evaluation of nutritional status, metabolic outcomes, overall complication rates and quality of life, within 2 years after surgery. Key inclusion criteria are obese patients with body mass index (BMI) ≥40 kg/m2 or ≥35 kg/m2 with at least one comorbid condition and candidate to a first bariatric procedure or after failure of sleeve gastrectomy. Patients randomised by minimisation in two arms, based on centre, surgery as a revisional procedure, presence of type 2 diabetes and BMI >50 kg/m2 will be included over 2 years.A sample size of 166 patients in each group will have a power of 90% to detect a probability of 0.603 that excess weight loss in the RYGB arm is less than excess weight loss in the SADI-S arm with a 5% two-sided significance level. With a drop-out rate of 10%, it will be necessary to include 183 patients per group.Ethics and dissemination The study was approved by Institutional Review Board of Centre Hospitalier Universitaire Morvan (CPP1089-HPS1). Study was also approved by the French national agency for drug safety (2018061500148). Results will be reported in peer-reviewed scientific journals.Trial registration number NCT03610256.